The Role of the Church in Promoting Human Rights in Nigeria - Enemali, Aloysius (Cultural and religious studies, 2022)
This article discusses the role of the Church in promoting human rights in Nigeria. This is anchored on the fact that the Church must live according to what it proclaims to the world especially against an avalanche of serious abuse of human rights in Nigeria. Cases abound how innocent citizens die in the hands of terrorist groups or communal clashes. This implies that it must live by the standards of the Gospel of Christ, striving vigorously to make the Christian values of love, honesty, truth, forgiveness, justice, self-sacrifice, solidarity and compassion guide the dealings with members with others in their private and public lives. It must be a Church that upholds the dignity and rights of human person and denounces what is essentially inhuman. Using descriptive and analytical methods, the paper underscores that the Church especially the canonists must courageously fight against forces of evil and iniquity engaging all stakeholders to a continuous dialogue that enhances mutual understanding and cooperation. In this way, all stakeholders will respect and uphold the sanctify of human rights in Nigeria and beyond.